Pengaruh Beberapa Jenis Pakan Terhadap Pertumbuhan Populasi Brachionus spp The Effect of Some Types of Food to Brachionus spp Population Growth - Henny Fitriani S; Darma Bakti; Nurmatias Nurmatias (AQUACOASTMARINE, 2014)
Natural food that has a high protein content, easily digestible and small sized could be found in Rotifers genus Brachionus. However, due to the complication of cultivating, it has low rate production. The purpose of this research was to identify appropriate food and to idenfity maximum time of rotifer’s growth The methods used experimental and observation by directly observing the population growth of Brachionus spp. The experiment using a Completely Randomize Design with 4 treatment and 3 repetition. Four treatments include A (Brachionus spp + phytoplankton), B (Brachionus spp + soya bean production waste), C (Brachionus spp + baker”s yeast), dan D (Brachionus spp + vitamin B-Complex).The result showed that there were different population of Brachionus spp to each treatment. The highest population could be found in the soya bean production waste with population value 201x104 ind/ml. The highest population was reached in the eighth day. It revealed that Branchionus spp with high value could be produced in the soya bean production waste and the optimum time was in the eighth day after the spreading.Keywords: Brachionus spp, Population Growth, Soya Bean Production